Hormonal regulation of transcription of rDNA: use of nucleoside thiotriphosphates to measure initiation in isolated nuclei. - Zhang, Z Y (1984)
Nuclei isolated from cultured mouse and rat cell lines initiated pre-rRNA chains at the correct site and with the correct nucleotide specificity (A for mouse, G for rat). Nucleic acid filter hybridization and S1 nuclease mapping were used to analyze the RNA products initiated with nucleoside (beta-S)triphosphates. Initiation of pre-rRNA was completely resistant to alpha-amanitin but was inhibited by either actinomycin D or heparin. Experiments with P1798 mouse lymphoma cells indicated that the antiproliferative effects of glucocorticoids on lymphoid cells includes a reduction in the ability of nuclei to initiate pre-rRNA chains.